STRATEGY ANALYSIS OF GINGER PLANT DEVELOPMENT IN PANDERMAN FOREST FARMERS GROUP, BATU CITY USING SWOT METHOD - Tirta Yoga; Anung Prasetyo Nugroho; Karunia Setyowati Suroto (Agripreneur : Jurnal Pertanian Agribisnis, 2024)
This study aims to evaluate the potential of ginger cultivation in the Panderman Forest Farmer Group (KTH Panderman) and to formulate strategies for developing ginger cultivation at the site. The research method used is SWOT analysis, with data collected through observation, interviews, questionnaires, accredited sources, and documentation. The results show that based on the IFAS and EFAS matrices, the weighted scores for strengths, weaknesses, opportunities, and threats are 1.77, 1.99, 2.13, and 1.04, respectively. In the SPACE matrix analysis, the Y-axis score is 1 and the X-axis score is 2, which places the strategy in the aggressive quadrant. This indicates that ginger cultivation in KTH Panderman has strong potential for development, with a favorable position to leverage internal strengths and external opportunities. The conclusion of this study is that ginger cultivation in KTH Panderman has significant potential, as reflected by its position in the aggressive strategy quadrant. The recommended development strategies for ginger cultivation include increasing production by utilizing human resources and local government support for infrastructure, improving production techniques, providing agricultural technology training, building water storage facilities, enhancing transportation options, and following guidance from agricultural extension workers.